Dental caries and fluorosis among children in Lebanon - Mounir Doumit; Bassel Doughan (Wolters Kluwer Medknow Publications, 2018)
Purpose: The purpose of this study is to assess caries and enamel fluorosis in a sample of 1433 children aged 6-8, 12, and 15 years from 48 schools in 6 regions of Lebanon, selected by probability proportional to size. Methods: Children were examined according to the World Health Organization criteria. Results: Our results showed a mean of decayed, missing, and filled teeth (DMFT) of 0.6 (dft of 5.15), 3.42, and 5.44 corresponding respectively to the groups of 6-8-, 12-, and 15-year-old children. In the same groups, the percentage of DMFT = 0 for the 6-8-year-old category was 74%, the 12-year-old category was 20.9%, and for the 15-year-old category was 9.7%; Ten (2.1%) 12 year olds had moderate and one (0.2%) severe scores; these children had been born in other countries. Conclusions: Survey results confirm the need to implement nationwide dental caries prevention measures. Since water fluoridation is not feasible, salt fluoridation would be the alternative.